The Impact of Covid-19 on Women's Mental Health and Wellbeing During Pregnancy and the Perinatal Period: A Mixed-Methods Systematic Review - Kanamon Pankaew PhD; Diane Carpenter PhD; Nalinee Kerdprasong PhD; Juntina Nawamawat PhD; Nisa Krutchan PhD; Samantha Brown MSc; Jill Shawe PhD; Jane March-McDonald PhD (SAGE Publishing, 2024)
Review Question: What is the impact of Covid-19 upon the mental health and well-being of women during pregnancy and during the perinatal period? Inclusion criteria: empirical primary research; maternal mental health and wellbeing; perinatal period; Covid-19; English or Thai language; studies from December 2019-September 2021, updated March 2024. Exclusion criteria: secondary research, commentary, grey literature. Databases searched: CINAHL, Cochrane, JBI, Medline, PsycINFO, Clinical Key and Web of Science. Studies were assessed for bias using tools aligned with study design. A convergent integrated approach was taken whereby quantitative data was combined with qualitative data, synthesised simultaneously using Braun and Clarke Six Steps to Thematical Analysis and presented as narrative. Forty-two studies were included. Overall level of methodological quality of studies was 14 rated good, 28 fair. Overarching themes: "Impact" and "Emotional Impact." Themes: demographic impact; mental health and socio-economic factors; obstetric factors; pre-morbidity; maternity service delivery; relationships; fear and worry, grief and loss. Commonality suggested some evidence for increased risk and prevalence for perinatal mental illness to pre-pandemic levels. Risk factors: lack/perceived lack of social support; high-risk pregnancy, complex obstetric history; prior mental illness; maternity service delivery, quality and safety; fear and worry. Results confer perinatal mental illness prominent during the pandemic though many did not suggest prevalence higher than pre-pandemic levels, or directly associated. Several factors compound risk. A small number of protective factors are identified. The dynamic processes of risk and protection need to be understood within the specific context in which they operate. The authors received no financial support for the research, authorship, and/or publication of this article. The study was not registered.